صورة سلطنة عمان في الصحافة الجزائرية المعاصرة - جهلان، محمد بن أحمد; بوحجام، محمد بن قاسم بن ناصر Bouhejam, Mohammed bin Qassem bin Nasser (جامعة السلطان قابوس - كلية الآداب والعلوم الاجتماعية, 2018)
This study tried to dive in the archives relating to Oman in the Algerian contemporary press, (1986-2016), and its goal is to look for the Oman presence in the Algerian press, and its role in consolidating of Algeria’s Oman relations in the past and present. Based on the above, we have attempted in this study to analyze the subject - after a systematic approach- in the following topics: 1. Introduction to the interesting of Algerian journalists about Oman in modern-day. 2. Algerian press and the contemporary cultural scene in Oman. 3. Algerian press and document the views of the Algerian and Omani on topical issues. Among the findings of the research is the extrapolation of the huge amount of Algerian press material covered by the period of study. That the reasons of Omani-Algerian relationship extend in the depths of history, back to the second century AH, and she has stimulated the efforts of the press pioneers in Algeria and Zanzibar this relation and contributed to its consolidation in this modern age. The study also concluded that the image of the Sultanate of Oman in this press embodies a mosaic of high cultural characteristics. The first is: Oman’s adherence to its religious and Arab identity. The second is: his struggle for his freedom and his struggle against colonialism throughout history. The third is: the wrapping of the Omani people around their political leadership and their pride in their scientists. The fourth: the sense of citizenship and co-existence and the entrenchment of the right to difference. The fifth: focus in the renaissance on the humans before the structures, and finally, the image of the Sultanate of Oman in short is: “Is the originality of history, the renaissance of the future, and a worthy example to study and follow-up”.
حاولت هذه الدراسة الغوص في أرشيف متعلق بسلطنة عمان في الصحافة الجزائرية المعاصرة (من أواسط الثمانينيات إلى اليوم)، وتهدف إلى البحث عن الحضور العماني في الصحافة الجزائرية، وأثر هذا الحضور في رسم صورة حول سلطنة عمان لدى القارئ الجزائري، مما يسهم في توطيد العلاقات الثقافية والفكرية بين شعبي البلدين الشقيقين. بناء على ما تقدم؛ فقد حاولنا في هذه الدراسة معالجة الموضوع بعد توطئة منهجية في عناصر ثلاثة: أولا: جذور الحضور العماني في الصحافة الجزائرية ومحفزاته. ثانيا: حضور سلطنة عمان في الصحافة الجزائرية الحديثة والمعاصرة: (الشروق، الخبر، السلام...). ثالثا: خلاصات عن صورة سلطنة عمان في الصحافة الجزائرية (في حوالي قرن من الزمن). ومن بين النتائج التي توصل إليها البحث من استقراء الكم الهائل من المادة الصحفية الجزائرية التي غطتها فترة الدراسة، أن مسوغات التواصل العماني الجزائري ضاربة في أعماق التاريخ تعود إلى القرن الثاني الهجري وقد حفزت جهود رواد الصحافة في الجزائر وزنجبار هذا التواصل ووطدته في العصر الحديث. كما خلصت الدراسة إلى أن صورة سلطنة عمان في هذه الصحافة تجسد لوحة فسيفسائية من المميزات الثقافية الرفيعة، أولها: تمسك العماني بهويته الإسلامية والعربية. ثانيها: استماتته من أجل حريته ومقارعته للاستعمار عبر التاريخ. ثالثها: التفاف الشعب العماني حول قيادته السياسية واعتزازه بعلمائه. رابعها: حس المواطنة الراقي وتكريس الحق في الاختلاف. خامسها: التركيز في النهضة على الإنسان قبل البنيان. وأخيرا فإن صورة سلطنة عمان توجز باختصار في عبارة: "هي أصالة التاريخ، ونهضة المستقبل، ومثال جدير بالدراسة والاقتداء".
Keywords: وسائل الإعلام -- الصحافة والإعلام -- الصحافة الجزائرية المعاصرة -- سلطنة عمان -- المجتمع العماني